Preparation And Characterization Of Piper Betle Nanoemulgel - Noor Amirah Syamimi Binti Mat Radzi (2021)
The purpose of this research is to study the characterization of nanoemulgel which encompasses the usage of Piper belle essential oil as bioactive ingredient. The Piper belle oil were extmcted using stcam distillation method from Piper belle leaves. The compounds of the Piper betle oil were examined using Fourier Transform Infrared Spectroscopy (FTIR) which showed the existence of 2-allyI-4-methylphenol, eugenol, 4-(pentyloxy)phenol, 2.2'-diallybisphenol, isoeugenol and 1,2-difluorobenzene. The Piper belle essential oil then incorporated into oil phase of two different total weight of nanoemulsion of 4g (NE2) and lOg (NE3) where the NE3 formulation remain stable for longer period than NE2 formulation. With addition of hydrogel into nanoemulsion, forming nanoemulgel. The characteristics of NEI and NE3 nanoemulsion and NEG and NEG3 nanoemulgel were studied using Dynamic Light Scattering where the result of Z-average, polydispersity index and zeta potential showed NEGI has the ITIOSI ideal result following by NEG3. Stability test showed NEI was the most stable for nanoemulsion where. all nanoemulgel is stable for four weeks. The spreadibility of nanoemulgel showed NEG3 has the biggest diameter thus its viscosity is presumed to be lowest as the spreadibility of formulation are affected by the viscosity of the nanoemulgel.